Pengaruh Kondisi Kerja Tidak Ergonomi Terhadap Keluhan Musculoskeletal Disorders Pada Pekerja Finishing Di PT Wika Gedung Depok - Baiq Novita Anggraini Djuarsah; Herlina Herlina (STIKes Persada Husada Indonesia, 2018)
Musculoskeletal disorders (MSDs) are a condition that results from trauma experienced by the body over a period of time. The purpose of this study was to determine the effect of ergonomic work factors on musculoskeletal disorders complaints on finishing workers at PT Wika Building Depok. Place of research in PT Wika Building Depok. This research is a quantitative analytic research using quantitative approach, using questionnaire and using Rapid Entire Body Assessment (REBA) method. Population in this research is finishing construction worker at PT Wika Building Depok. Independent variableswork conditions. Dependent variable musculoskeletal disorders complaints. The results obtained from this study are the significant influence between the working period (p-value = 0.001), history of musculoskeletal disorders (p-value = 0.002), posture at work (p-value = 0,000), duration of work (p-value = 0,003), workload (p-value = 0,004), work frequency (p-value = 0,003) with musculoskeletal disorders complaints on finishing workers at PT Wika Building Depok Year 2018. From the results of this study concluded that the higher the risk work conditions is not ergonomics increasingly affect the complaints musculoskeletal disorders on finishing workers in PT Wika Building Year 2018.